Non-Invasive Monitoring of Blood Glucose Concentration Based on Insulin Secretion Level Using NIR Spectroscopy for Diabetes Detection (Medico Legal Update, 2021)
Diabetes claims millions of lives every year. Diabetes Mellitus is a metabolic disorder that occurs due tothe increase in blood sugar level. The blood sugar level control by insulin secreted from pancreas. Thediabetes classify as type 1 and type 2 depending on insulin secretion. The type 2 diabetes is more commonin people than type 1 diabetes. Traditionally, the blood glucose level estimate with glucometer and bloodtest. However, the test require invasive blood pricking for blood glucose measurement. The measured bloodglucose value also varies due to amount of blood taken for testing, part of blood used for testing, depth offinger pricking, physical activity, stress and underlying illness. Hence, the insulin secretion from pancreasmonitor for accurate prediction of blood glucose level. The blood glucose level varies with respect to insulinsecretion from pancreas. In this paper, we propose a non-invasive approach to estimate blood glucoseaccurately through NIR spectroscopy for diabetes control. The NIR spectroscopy signal obtained frompancreas process through Rational Dilation Wavelet Transformto determine the insulin secretion level. Thenon-invasive NIR spectroscopy method measures glucose level with 90% accuracy compared to lab results.